Epistolary Genre in Works of Maxim Gorky: Correspondence with V. F. Khodasevich (1924–1925) - M. G. Urtmintseva (Научный диалог, 2025)
This article investigates the characteristics of the epistolary genre within the correspondence of Maxim Gorky during the years 1924–1925. This period marks a time of vibrant creative exchange with V. Khodasevich, a prominent figure in Russian cultural emigration. The aim of the study is to demonstrate that Gorky’s letters to Khodasevich represent a creative act emerging from their brief yet impactful epistolary interaction. The analysis reveals that these letters constitute an individual genre structure, showcasing the author’s innovative approach to the genre as a dynamic entity characterized by both stable narrative-compositional techniques and varied methods of addressing the recipient, reflecting the uniqueness of the creative process involved in composing the letters. The research highlights how the complex array of textual creation methods employed in Gorky’s letters is influenced by the personalities of the correspondents, the nature of the era, and the circumstances surrounding their correspondence. It identifies consistent formulas in Gorky’s epistolary communication with Khodasevich, particularly those developed during discussions on the publication policies of the journal “Beseda.” The novelty of this study lies in its demonstration of the multifunctionality of polite discourse strategies in written dialogue, the associative nature of narrative dynamics, the use of various types of supertext, and the focus on how the text is perceived by its recipient.